Primary Renal Epithelioid Hemangioendothelioma - Roy, S. (Hindawi Publishing Corporation, 2012)
Epithelioid hemangioendothelioma is a rare vascular tumor with intermediate biologic behavior and metastatic potential. Primary renal epithelioid hemangioendothelioma is extremely rare and we present the second report of this rare tumor in an interesting clinical scenario. A 59-year-old male with established history of widely metastatic high grade esophageal adenocarcinoma was found to have an isolated renal nodule on a followup computed tomography (CT) scan. Surgical excision, with the suspicion of metastatic carcinoma, and subsequent pathologic examination revealed an epithelioid hemangioendothelioma. The various differential diagnoses and use of morphological clues and immunohistochemistry are discussed.